2020
DOI: 10.7573/dic.2020-4-13
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections in the elderly: a review of disease characteristics and current treatment options

Abstract: Urinary tract infections (UTIs) are common in the elderly, and cover a range of conditions from asymptomatic bacteriuria to urosepsis. Risk factors for developing symptomatic UTIs include immunosenescence, exposure to nosocomial pathogens, multiple comorbidities, and a history of UTIs. European guidelines on urological infections recommend antimicrobial treatment only for symptomatic UTIs. Non-antimicrobial options to treat and prevent UTIs include among others cranberry products, OM-89 Escherichia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 50 publications
1
26
0
4
Order By: Relevance
“…A high quota was observed in seniors between 60–69 years old, representing 24.73% in females and 30.07% in males, with a peak of incidence in patients over 70 years old—48.28% in the overall population. It has been shown that multiple risk factors are associated with the prevalence of UTIs in the elderly male population, such as prostate enlargement, urolithiasis, urinary tract neoplasia, renal failure, or urethral strictures [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high quota was observed in seniors between 60–69 years old, representing 24.73% in females and 30.07% in males, with a peak of incidence in patients over 70 years old—48.28% in the overall population. It has been shown that multiple risk factors are associated with the prevalence of UTIs in the elderly male population, such as prostate enlargement, urolithiasis, urinary tract neoplasia, renal failure, or urethral strictures [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of UTI increases in patients aged 40 years and over with the highest peak in the 50-59year age group in long-term care facilities and communities (Matthews and Lancaster 2011). Several predisposing factors cause UTI in elderly people, including prostate problems in men, postmenopausal estrogen deficiency in women, exposure to nosocomial pathogens, and comorbidities such as diabetes mellitus is widely associated with an increased incidence of UTI (Ahmad et al 2020;Rodriguez-Mañas 2020). In terms of gender, similar to previous findings by Kurniawati and Auliyanah (2021), women are more likely to have urinary tract infections compared to men in all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…With age, the incidence of urinary tract infections increases [ 34 ]. In addition to symptomatic urinary tract infections, asymptomatic bacteriuria is common among the elderly.…”
Section: Peri-operative Managementmentioning
confidence: 99%